К реакклиматизации свиньи дикой (Sus scrofa L.) в Крыму - Кормилицын, А.А.; Дулицкий, А.И. (Вестник зоологии, 1972)
The article contains the materials on introduction history, ecology, morphology of Sus scrofa La in the Crimea. The dynamics of the species quantity there from 1957 to 1969 is presented. Craniametric indices are given of 8 adult males, two adult females and 5 young animals al the age of 4--19 months. The list of their ecto- and endoparasiles. is presented.